Comparison of Post Operative Morbidity between Laparoscopic and Open Appendectomy in Children - Saha, N; Saha, DK; Rahman, MA; Islam, MK; Aziz, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):348-52. The abstract of this article is available on the PubMed website